Inductively actuated micro needles for on-demand intracellular delivery - Kavaldzhiev, Mincho N. (Sci Rep, 2018)
Methods that provide controlled influx of molecules into cells are of critical importance for uncovering cellular mechanisms, drug development and synthetic biology. However, reliable intracellular delivery without adversely affecting the cells is a major challenge. We developed a platform for on-demand intracellular delivery applications, with which cell membrane penetration is achieved by inductive heating of micro needles. The micro needles of around 1 μm in diameter and 5 μm in length are made of gold using a silicon-based micro fabrication process that provides flexibility with respect to the needles’ dimensions, pitch, shell thickness and the covered area. Experiments with HCT 116 colon cancer cells showed a high biocompatibility of the gold needle platform. Transmission electron microscopy of the cell-needle interface revealed folding of the cell membrane around the needle without penetration, preventing any delivery, which was confirmed using the EthD-1 fluorescent dye. The application of an alternating magnetic field, however, resulted in the delivery of EthD-1 by localized heating of the micro needles. Fluorescence quantification showed that intracellular delivery, with as high as 75% efficiency, is achieved for specific treatment times between 1 and 5 minutes. Overexposure of the cells to the heated micro needles, i.e. longer magnetic field application, leads to an increase in cell death, which can be exploited for cleaning the platform. This method allows to perform intracellular deliver by remotely activating the micro needles via a magnetic field, and it is controlled by the application time, making it a versatile and easy to use method. The wireless actuation could also be an attractive feature for in-vivo delivery and implantable devices.